2012
DOI: 10.1002/art.34600
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inflammation, bone destruction, and osteoproliferation in the HLA–B27/human β2‐microglobulin–transgenic rat model of spondylarthritis

Abstract: Objective Inhibition of inflammation and destruction but not osteoproliferation in spondyloarthritis (SpA) patients treated with anti-TNF raises the question of how these three processes are interrelated. This study aimed to analyze this relationship in a SpA rat model. Methods Histological spine and joint samples of HLA-B27/Huβ2m transgenic rats were analyzed for signs of spondylitis and destructive arthritis and semi-quantitatively scored as mild, moderate or severe inflammation. Results In spondylitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 41 publications
5
50
0
1
Order By: Relevance
“…However, this hypothesis does not fit with animal models demonstrating that complete inhibition of inflammation-driven bone destruction does not inhibit osteoproliferation, questioning the concept of reparative bone formation (Lories et al, 2008;Schett et al, 2009). Moreover, detailed analysis of the pathology of HLA-B27 transgenic rats, a spontaneous model of human SpA, shows that osteoproliferation occurs simultaneously with inflammation and destruction (Van Duivenvoorde et al, 2012). Finally, long-term clinical observations indicate that TNF blockade in established AS does not lead to new bone formation (Baraliakos et al, 2013).…”
Section: The Tnf-brake Hypothesismentioning
confidence: 93%
“…However, this hypothesis does not fit with animal models demonstrating that complete inhibition of inflammation-driven bone destruction does not inhibit osteoproliferation, questioning the concept of reparative bone formation (Lories et al, 2008;Schett et al, 2009). Moreover, detailed analysis of the pathology of HLA-B27 transgenic rats, a spontaneous model of human SpA, shows that osteoproliferation occurs simultaneously with inflammation and destruction (Van Duivenvoorde et al, 2012). Finally, long-term clinical observations indicate that TNF blockade in established AS does not lead to new bone formation (Baraliakos et al, 2013).…”
Section: The Tnf-brake Hypothesismentioning
confidence: 93%
“…The entheseal proliferation and inflammatory infiltrate were minor in this model and treatment with glucocorticoids [156], but not etanercept [157], did ameliorate inflammation somewhat but had no effect on the ankylosis. In a longitudinal study in HLA-B27/h2m transgenic rats, osteoproliferation was found external to the joint space separate from inflammatory infiltrates [139]. However, osteoproliferation and inflammation in HLA-B27/h2m transgenic rats were presented simultaneously suggesting distinct but parallel processes.…”
Section: -45 Statisticsmentioning
confidence: 94%
“…The initial symptom is gastrointestinal inflammation followed by other inflammatory features present in SpA, such as peripheral arthritis, spondylitis, enthesitis and psoriasis [138]. In addition to inflammation, chondrocyte proliferation and syndesmophyte formation, were observed in the peripheral joints and spine [139]. The copy number of HLA-B27 and h2m molecules has a threshold effect on the susceptibility to spontaneous arthritis/spondylitis.…”
Section: -51 Hla-b27/h2m Transgenic Ratmentioning
confidence: 99%
See 2 more Smart Citations